2021
DOI: 10.1186/s40104-021-00605-y
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves the first cleavage of parthenogenetic embryos from vitrified–warmed mouse oocytes potentially by promoting cell cycle progression

Abstract: Background This study investigated the effect of melatonin (MT) on cell cycle (G1/S/G2/M) of parthenogenetic zygotes developed from vitrified-warmed mouse metaphase II (MII) oocytes and elucidated the potential mechanism of MT action in the first cleavage of embryos. Results After vitrification and warming, oocytes were parthenogenetically activated (PA) and in vitro cultured (IVC). Then the spindle morphology and chromosome segregation in oocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 74 publications
2
21
0
Order By: Relevance
“…Melatonin regulated the level of p-Drp1 Ser616 to alleviate stress-induced damage, promoting cell development and functional recovery. Cryopreservation has been implicated in mitochondrial damage and reduced vitality (2,14,38,45). TOMM20 is a marker of mitochondrial (46,47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melatonin regulated the level of p-Drp1 Ser616 to alleviate stress-induced damage, promoting cell development and functional recovery. Cryopreservation has been implicated in mitochondrial damage and reduced vitality (2,14,38,45). TOMM20 is a marker of mitochondrial (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of red fluorescence to green fluorescence was recorded as MMP ( ψm) of oocytes. The intensity of red and green fluorescence in each oocyte was measured using Image J software (Version 1.48; National Institutes of Health, Bethesda, MD, USA), calculated the fluorescence intensity was based on previous study (2,38,42).…”
Section: Detection Of Mmp and Atp Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin upregulates the primary implantation receptors, ErbB1 and ErbB4, and significantly reduces intracellular ROS in mouse blastocysts (increasing the embryo total antioxidant capacity) and promotes mitosis of the inner cell mass and trophectoderm cells [ 58 ]. Recently, it has been demonstrated that the supplementation of culture medium with melatonin (10 −9 mol/L) improves the growth of mouse parthenogenetic embryo potentially by promoting cell cycle progression [ 59 ]. Despite all these functions, melatonin is not present in culture media used in ART.…”
Section: Abnormal Placentation and Art: Molecular Factors And Involved Signalingmentioning
confidence: 99%
“…This suggests that cryopreservation could damage the development of calcium transients at fertilization [ 18 ]. There have been many pre-clinical level research studies that mainly sought to improve mitochondrial biogenesis [ 19 ], decrease ROS production [ 20 ], and reestablish Ca 2+ ion regulation [ 21 ] in cryopreserved oocytes. Although these pre-clinical studies showed some improvement in embryo development, none have been able to restore the damaged oocyte mitochondria following cryopreservation.…”
Section: Introductionmentioning
confidence: 99%